SYNTHESIS OF CARBOXYMETHYL CELLULOSE FROM RICE HUSK - JARMKOM, KHEMJIRA; KHOBJAI, WARACHATE; TEACHAOEI, SURACHAI; SHUWISITKUL, DUANGRATANA (International Journal of Applied Pharmaceutics, 2021)
Objective: The purpose of this research was to produce carboxymethyl cellulose from rice husk (CMCRH) and used it as a raw material in food or health products. Methods: Cellulose was extracted from husk rice and converted to CMC (CMCRH) using sodium hydroxide (NaOH) and monochloroacetic acid in isopropanol (C3H8O). Results: CMCRH was characterized for chemical composition and morphology by scanning electron microscopy. Microscopy analysis showed that chemical composition changes with increasing sodium content (Na-). Likewise, morphology has changed. Physicochemical and viscosity tests showed that were similar properties compare with commercial CMC. Conclusion: CMC is derived cellulose that is used in products for various applications. RH is an agricultural waste that is carried out to synthesize CMC (CMCRH). Finally, CMCRH has the potential to be used in raw materials in food or health products which biodegradable material.